Lucky Luke. 9, The wagon train - Goscinny, 1926-1977.; Morris, 1923-; Spear, Luke (Canterbury, Kent [England] : Cinebook, 2008)
Lucky Luke is asked to step in for an ill-tempered driver on a wagon train to California, but the former driver vows revenge on both the wagon train and Luke.
First published: Paris: Dargaud Editeur, c1971, under title: Lucky Luke: La caravane.
Spine title.
Translated from the French.
2.9
3-6.
3-6
Keywords: Cowboys -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Wagon trains -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Lucky Luke (Fictitious character). -- Fiction; Wagon trains -- Fiction; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Graphic novels; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Wagon trains -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Fiction; Graphic novels; Western comic books, strips, etc